21st‐Century Mangrove Expansion Along the Southeastern United States - Lucia I. A. Enes Gramoso; Dustin Carroll; Kyle C. Cavanaugh; Remi Bardou; Michael J. Osland; Tom Van der Stocken (Global Change Biology, 2026)
Warming winter temperatures are driving range expansion of tropical, cold‐sensitive mangroves into temperate ecosystems. Along the Atlantic coast of North America, the mangrove range limit is particularly sensitive to climate variability and historical data demonstrate that the mangrove‐salt marsh ecotone on this coast has shifted recurrently during recent centuries. However, a comprehensive understanding of how this mangrove‐salt marsh ecotone may shift in the future remains lacking. Here, we combine ensemble forecasting of mangrove distribution for the next century with high‐resolution oceanographic dispersal simulations, phenological observations, and historical hurricane data to project future mangrove‐salt marsh dynamics at the rapidly changing range limit in northeastern Florida (USA). We show that warming winter temperatures will drive continued poleward expansion of mangroves along North America's Atlantic coast, potentially reaching South Carolina by 2100. With ongoing climate change, suitable mangrove habitat is projected to expand beyond the current range limit, and dispersal simulations suggest successful colonization of these sites from established mangrove populations. Additionally, patterns in hurricane directionality and intensity and field reports of propagule presence reveal that these high‐energy events may significantly contribute to future mangrove range expansion by facilitating long‐distance, storm‐driven propagule dispersal. The encroachment of mangroves in salt marsh‐dominated latitudes is expected to substantially modify wetland ecosystem function and structure, emphasizing how the identification of newly colonizable habitat can inform conservation strategies and site‐specific decisions on mangrove management.

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Ocean-Ice Interactions in Inglefield Gulf: Early Results from NASA’s Oceans Melting Greenland Mission - Josh Willis; Dustin Carroll; Ian Fenty; Gurjot Kohli; Ala Khazendar; Matthew Rutherford; Nicole Trenholm; Mathieu Morlighem (Oceanography, 2018)